2021
DOI: 10.1016/j.lanwpc.2021.100226
|View full text |Cite
|
Sign up to set email alerts
|

Changes in systemic cancer therapy in Australia during the COVID-19 pandemic: a population-based study

Abstract: Background Since the emergence of COVID-19 there have been increasing global concerns about delays and/or discontinuations in cancer care. However, it is unclear to what extent systemic cancer therapy was impacted by COVID-19 in countries with relatively low COVID-19 infection rates. We examined changes in systemic cancer therapy in Australia during the COVID-19 pandemic. Methods We conducted a national observational study using de-identified records of government-subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…42 A similar finding was also described in Australia. 43 Similar to our findings in cervical palliative setting, Blay et al, 44 in their analysis of French data, reported an increase in the number of patients who initiated palliative treatment. In their analysis of the quantity of treatment and scheme of treatment changes, Eijkelboom et al 45 reported that chemotherapy was less likely to be performed against hormonal therapy for breast cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
“…42 A similar finding was also described in Australia. 43 Similar to our findings in cervical palliative setting, Blay et al, 44 in their analysis of French data, reported an increase in the number of patients who initiated palliative treatment. In their analysis of the quantity of treatment and scheme of treatment changes, Eijkelboom et al 45 reported that chemotherapy was less likely to be performed against hormonal therapy for breast cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
“…16 In Australia, where there was a low burden of COVID-19 at the time, any changes in the dispensation of chemotherapy was small and transitory, driven by immunotherapies and targeted therapies. 17 In contrast, the number of registrations for neoadjuvant-intent ST decreased in England and Italy due to COVID-19. 18,19 In the United Kingdom, following multidisciplinary consultation many patients with breast cancer had incomplete neoadjuvant chemotherapy or instead received adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Stockpiling has been observed internationally as well [ 21 , 22 ]. While to our knowledge there have been no reports of people with legitimate needs for these medicines being unable to access them [ 23 ], nor increases in adverse events, stockpiling does put pressure on medicine supply and may exacerbate shortages. This is particularly true during crises such as the COVID-19 pandemic which led to disruptions of the global supply chain through lockdowns, understaffing, and travel bans [ 24 ].…”
Section: Discussionmentioning
confidence: 99%